PROPOSED ORGANIZATIONAL STRUCTURE FOR AGRICULTURAL INITIATIVE MEDIA IN IRAQ - & Naji, AL-Hamadani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The current paper aims at building Proposed Organizational Structure For Agricultural Initiative Media in Iraq for observing the opinions of the employees working in the Agricultural initiative and those working in the media and agricultural sector on three levels as to measure suitability of Proposed informational Organizational Structure . In order to carry out goals of the research, a questionnaire has been prepared andincluded fifth scale consisting of 115 items distributed on 6 space and 22 axils. The research has been carried out on cluster random sample with 50% of all offirst. Iraqi governorates of southern, middle and northern (15) except Kurdistan governorates, withKirkuk governorate assign for the north (the area of the research) while Baghdad, Diyala, Karbala, Al-Najaf for the middle, and Basra,Maysan and The Qar for the south. Seconed.employees agriculturedistributedon three levels, the first level includes the supreme committee of agriculture initiative in the center and branch committees in the governorates, the second level includes informational department employees in directorates of agriculture and informational sector in agricultural training and instructions , while the third level includes agricultural employees working in the centers and agricultural departments . Through having the scale of informational organizational structure offered to the sample of the research , it has finally reached to items of building proposed organizational structure by using the following scale: the item within the finished form for building the structure has been obtained a larger average than the proposed average amounted (3 degree) ; the result was to remain all items in the final form for building the proposed informational organizational structure in all three levels of the research sample. Then, it has been reached to build the finished form of the proposed informational organizational structure of agricultural initiative Media. The researcher has recommended tonecessarily provide necessities to succeed this proposed informational organizational structure of agricultural initiative Media since being considered as a basic element for succeeding the High Committee of Agricultural Initiative.